2006
DOI: 10.2215/cjn.01751105
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization after Kidney Transplantation

Abstract: Kidney transplant recipients may develop de novo anti-HLA and non-HLA antibodies after transplantation. Although these antibodies may be donor-specific or non-donor-specific, their presence may increase the risk for acute and chronic rejection, thereby decreasing allograft survival. The introduction of more sensitive and specific methods to detect anti-HLA antibodies, such as Flow Specific Beads and FlowPRA, both before and after transplantation, will help to define immunologically high-risk kidney transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 63 publications
(52 reference statements)
1
46
1
1
Order By: Relevance
“…These findings suggest that all patients with strong DSA, whether class I or II, may need PP to decrease the load of circulating alloantibodies and the incidence of acute AMR. Previous studies, summarized in a recent review article (16), showed that both class I and II DSA can be associated with acute and chronic rejection. The acute rejection rate has been Ͼ30% in patients who receive desensitization protocols, and it is still not clear which protocol (high-dosage IVIG, PP/low-dosage IVIG), what type of induction treatment (Thymoglobulin, anti-IL-2R antibodies, alemtuzumab), or addition of rituximab is better for the prevention of early acute AMR.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that all patients with strong DSA, whether class I or II, may need PP to decrease the load of circulating alloantibodies and the incidence of acute AMR. Previous studies, summarized in a recent review article (16), showed that both class I and II DSA can be associated with acute and chronic rejection. The acute rejection rate has been Ͼ30% in patients who receive desensitization protocols, and it is still not clear which protocol (high-dosage IVIG, PP/low-dosage IVIG), what type of induction treatment (Thymoglobulin, anti-IL-2R antibodies, alemtuzumab), or addition of rituximab is better for the prevention of early acute AMR.…”
Section: Discussionmentioning
confidence: 99%
“…HLA antibodies can be present before transplantation, because of prior exposure to nonself HLA molecules (after pregnancy, blood transfusion or prior allo-transplantation), or can be produced de novo after transplantation (5). Donor-specific anti-HLA alloantibodies can initiate rejection through complement-mediated and antibody-dependent, cell-mediated cytotoxicity (6,7).…”
mentioning
confidence: 99%
“…Aunque algún estudio muestra asociación entre la reexposición a antígenos HLA no compatibles y menor supervivencia del injerto 16 , la mayoría de las series no aprecian diferencias en el número de incompatibilidades entre los diversos trasplantes 18,20,23 . En nuestro estudio la media de anticuerpos anti-HLA previo al segundo trasplante fue del 17%, aumentando significativamente respecto al primero 24,25 . Aunque clásicamente el incremento del porcentaje de anticuerpos anti-HLA previo a cada trasplante se asocia con una disminución de la supervivencia de los sucesivos trasplantes 26,27 , en nuestra experiencia el incremento en el porcentaje de anticuerpos anti-HLA no influye en la supervivencia del segundo injerto.…”
Section: Discussionunclassified